Total Anomalous Pulmonary Venous Return in Sulaimani, Iraq: A Retrospective Analysis of Pediatric Cases and Outcomes - Salih, Aso; Awrahman, Khalat; qadir, Trifa M. (Journal of Humanitarian Cardiovascular Medicine, 2024)
Background: total anomalous pulmonary venous return is a rare cyanotic congenital heart disease with bad outcome without appropriate intervention. In which all four pulmonary veins drain incorrectly to the right atrium. Aim of study: To determine the main morphological features and patient outcomes of isolated total anomalous pulmonary vein in pediatric heart diseases in Sulaimani center. Patients and method: A retrospective study including 46 patients aged from 15 days to 18 years has been performed in department of cardiology / Dr. Jamal Ahmad Rashid teaching hospital, Anwar Shekha hospital /HQ hospitals. The data were collected from the recorded files of the patients examined in that unit during the period from 2010 to 2022. Collected data include age, sex, family history, consanguinity, echo finding and outcome of the cases. Stoical analysis was done by SPSS21and P value of < 0.05 was regarded as significant. Results: there are (45.7%) supra-cardiac, (45.7%) intra-cardiac and (8.6%) infra-cardiac. Male to female ratio is 1:1. (58.7%) of patients are associated with ASD, and (6.5%) have mixed ASD and VSD. Pulmonary hypertension detects in (30.4%) of cases. Overall, (63.9%) of cases deceased and only (36.1%) are still alive. Median age of diagnosis for alive cases are 6.5 months (21 days to 21 months) and median age at repair are 15.6 months (one month to 10 years). Operation was conducted for (92.3%) of alive cases. Conclusion: supra-cardiac and intra-cardiac are detected equally, infra-cardiac is the least common type and mixed type was not detected. ASD is the most common congenital heart defect associated with TAPVR. . Only a third of cases survive, operation has been performed for most of them.